O efeito da perda de remuneração real sobre a demanda de consignados de servidores ativos e inativos do poder executivo do Município de Fortaleza - Tabosa, Carlos Henrique de Oliveira (2024)
This work aims to investigate the determinants of demand for payroll loans in February 2023, considering a context of real salary loss between 2019 and 2023 for part (25.9%) of municipal employees in Fortaleza CE. Using logistic and linear regression models, and an information base fro m the municipality's Department of Planning, Budget and Management, we investigated more specifically whether the existence and intensity of wage loss affects the demand and contracted value of payroll loans. The results revealed that wage loss influenced not only demand, but also the value of credit. For a salary loss of more than 10%, the demand for payroll loans increases on average by R$88.63, suggesting a compensating effect. Other variables such as age, length of service, gender, work group, and caree r also proved to be important cofactors in the demand for this type of credit.